Biostratigraphic implications of the Valanginian to Lower Hauterivian benthic foraminifers from the Vergol/La Charce composite Section (southeast France, Vocontian Basin) - Colpaert, Clémentine; Reboulet, Stéphane; Li, Gang (Annales de paléontologie, 2024)
The well-exposed Valanginian to Lower Hauterivian sequences of the Vocontian Basin (South-East France) are revisited based on a micropalaeontological study of material collected in the Vergol and La Charce sections. A total of 528 tests of benthic foraminifers were recorded in good state of preservation. A biometric analysis of the species Dorothia hauteriviana is proposed in order to identify its morphotypes and their biostratigraphic significance. This study aims to identify benthic foraminiferal assemblages and to propose an integrated biostratigraphy along the Valanginian to Hauterivian sequence of the Vergol and La Charce sections (Vocontian Basin). Two foraminiferal assemblages have been recognized. The Lenticulina nodosa foraminiferal assemblage ranges from the lower Valanginian to the basis of the upper Valanginian Saynoceras verrucosum ammonite standard zones (StZ). The Lenticulina busnardoi foraminiferal assemblage is recorded from the second half of S. verrucosum to the top of Neocomites peregrinus StZ. The current study shows that the Vergol and La Charce composite section represents a complete segment of Valanginian to Lower Hauterivian foraminiferal assemblages, and records several changes in taxonomic biodiversity and dynamics of population for this interval. - Résumé - Les séquences du Valanginian à l’Hauterivien inférieur exposées dans le bassin Vocontien (Sud-Est de la France) ont été revisitées sur la base d’une étude micropaléontologique issue des échantillons collectés dans les affleurements de Vergol et de la Charce (Drôme, France). 528 foraminifères ont été recensés et sont assez bien conservés. Une analyse biométrique basée sur des coquilles de Dorothia hauteriviana a été lancée afin de souligner l’importance biostratigraphique de ses différents morphotypes. Cette étude a pour but d’identifier les assemblages à foraminifères benthiques le long de la séquence Valanginienne-Hauterivienne, et de proposer une biostratigraphie intégrée des coupes de Vergol et de La Charce (bassin Vocontien). Deux assemblages à foraminifères benthiques ont été reconnus. L’assemblage à Lenticulina nodosa s’étend du Valanginien inférieur à la base de la zone standard à ammonite Saynoceras verrucosum du Valanginien supérieur. L’assemblage à Lenticulina busnardoi est actuellement enregistré depuis la seconde moitié de la zone à ammonite S. verrucosum jusqu’au sommet de la zone à Neocomites peregrinus. L’analyse ici présente montre que la section composite de Vergol et de La Charce représente l’ensemble des assemblages à foraminifères du Valanginien et de l’Hauterivien inférieur pour cette région, ainsi que les changements de taxonomie, biodiversité et dynamique des populations qui leur sont associés.
Gesehen am 27.03.2025